(untitled) (UNED Research Journal, 2023)
ABSTRACT. “Socio-agronomic classifiction of plantain-producing farms in the Caribbean region, Costa Rica.” Introduction: Plantain is a food for millions of people in developing countries, and in Costa Rica its production is mainly located in the Caribbean region, with 3 354 farms, with low productivity and little technological adoption. Despite being a crop present in 56% of the small farms in the Limon´s province, there are few studies on the conditions of the farms and the people who grow plantain. Objective: To prepare a typology of plantain farms in the Caribbean region of Costa Rica according to productivity. Methods: 342 surveys were applied to farmers in six counties, corresponding to 28% of the plantain farms affected by the flooding of 2015. Results: Three types of farms were found, type 1 are the most efficient due the use of supplies and profitability, they represented 10% of the total farms and had the highest annual yields 49MT/ha). These farms have 0,8 ha of plantain crops, with densities greater than 2 000plants/ha, use corms of 500 to 800g, apply ammonium sulfate, shore-up the plants, bag the bunches, renew the plantations every 1 to 2 years and the people who attend these plantations are under 50 years of age. On the other hand, 66% of farms are type 3, producing 18MT/ha/year. Conclusion: The farms of the six counties have significant differences, especially in cultivated area and productivity, with farms smaller than 1ha being the most efficient and most profitable, and those of Alta Talamanca being the most biodiverse with 79% managed under agroforestry systems. Finally, plantain is a vulnerable production system, mainly due to agronomic management, the few phytosanitary controls and the weak training received by farmers.